Consultation services at the commercial laboratories - Samori, T (Rinsho byori. The Japanese journal of clinical pathology, 1997)
Only few customers consult with their using commercial laboratories about how to interpret the laboratory examination results, or how to proceed the laboratory diagnosis. But there are many questions about the test item, methodology, time course, and how to collect a specimen, and also there are many complaints about the test results, methods, reference values and reporting styles. Therefore, most of the commercial laboratories set up the information desk instead of the consultation desk. In our laboratory, Japan clinical laboratories, Inc., information services are done by not only the information telephone desk, but also the persons who go to the customers office(clinics or hospitals) for sales of the tests or collection and delivery of the samples. In this report, our information services were analyzed with the questionnaire and hearing to the sales and laboratory division, and with the records of the transaction of complaints(past 3 years) and the information service daily reports(past 2 months). From the results of the above analyses, it was observed that the commercial laboratory customers, e.g. clinicians, nurses, hospital clerks and medical technologists, have many various questions and complaints to the tests and the laboratories. And it was revealed that the education of the both staff of sales and laboratory division in the commercial laboratory is one of the most important subjects. For more effective use of the laboratory tests, clinical pathologists and medical technologists have to guide and supervise the commercial laboratories more adequately.